Ensino Médio Integrado: Educação E Trabalho Na Perspectiva Dos Estudantes Do Instituto Federal De Educação, Ciência E Tecnologia De São Paulo - Scherdien, Graciela Goncalves [UNIFESP] (2017)
Our goal is investigating the main conceptions about the vocational technical education integrated to the high school at the Federal Institute of Education, Science and Technology of São Paulo. For this, we considered the perceptions, conceptions and expectations of the students’ course in relation to the educational process, the school space and the formation for the work. We, thus, developing an analysis of the categories of work and the world of work, which are directly related to integrated education. Integrated training opposes instrumentalised education, the first formation does not reduce or simplify knowledge, it does not fragment individuals between those who execute and those who direct or plan the work: it proposes to overcome the fragmentation between theory and practice, enabling the construction of knowledge and Critical thinking. We discussed some apprehensions about integrated high school and how its functioning is internalized by these students. We have developed a qualitative research, of an ethnographic type, in which students of technical education integrated to secondary education could present their ideas, perceptions and expectations about this education system. These reports present possible failures or correct implementation of integrated teaching, as well as the existing contradictions. Integrated training is not only an articulation between high school and technical education, it is related: to the didactic-pedagogical relationships built during the educational process; Forms of appropriation of school space; And labor relations. Therefore, the interviews of these students were our main source to approach the practical aspects of the implementation of integrated secondary education, although we supplemented them with data from previous research. The analysis of these interviews showed that there is a heterogeneity in the socioeconomic profile of these students, with the predominance of young people in search of a good education, even if with a series of difficulties in relation to the behavior. There is also a series of contradictions regarding integrated teaching: on the one hand there is an effort on the part of the school group to put into practice the actions that could facilitate this integration, on the other hand many individuals do not have involvement or knowledge about teaching integrated. Most students interviewed showed that they understand integrated education more as a joint than an integration, but some practices and thoughts also contribute to the implementation of integrated education, even in a still primary and immature way; They problematized the didactic-pedagogical practices that collaborate or hinder the integration between high school and technical education. Observations and conversations with the students allowed us to broaden the discussion about the implementation of integrated secondary education, and we concluded that if we cannot consider the integration of effective teaching in the Institution, we cannot say that there is no integration at all a misconception. Therefore, we tried to present some possible interpretations in relation to this broad theme, in order to contribute to a better understanding of the profile of these students, and also to highlight some mechanisms to be adopted that can help in the implementation, maintenance or improvement of integrated teaching.